Polynomial Based Scheme for Secure SCADA Operations. (2015) - Pramod T.C.,; Sunitha, N.R.
Abstract: Supervisory Control and Data Acquisition (SCADA) systems are widely used in critical infrastructures and contemporary industrial processes. The advancements and increased interconnections lure the adversary to plunder the reliable operations of these systems. As the persistent monitoring and remote control is necessary to ensure reliable operations of the system, fortifying the security features of SCADA systems is crucial. In this paper, by considering the efficiency requirements in such networks, we propose a key establishment scheme for SCADA systems based on polynomial key distribution scheme. In this new approach, secret key is not transmitted in the network for any device to device communications. The proposed key establishment scheme supports broadcasting, multicasting, join and leave operations and secure communications between and across MTU-SUBMTU-Field devices of SCADA systems. The scheme also considers the constraints such as communication overhead, performance, bandwidth and accuracy to provide an elegant key establishment scheme for SCADA systems.